2018
DOI: 10.1155/2018/8746349
|View full text |Cite
|
Sign up to set email alerts
|

Traditional Chinese Medicine for Refractory Nephrotic Syndrome: Strategies and Promising Treatments

Abstract: Refractory nephrotic syndrome (RNS) is an immune-related kidney disease with poor clinical outcomes. Standard treatments include corticosteroids as the initial therapy and other immunosuppressants as second-line options. A substantial proportion of patients with RNS are resistant to or dependent on immunosuppressive drugs and often experience unremitting edema and proteinuria, cycles of remission and relapse, and/or serious adverse events due to long-term immunosuppression. Traditional Chinese medicine has a l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 57 publications
1
25
0
Order By: Relevance
“…is indicates the importance of blood stasis syndrome and Qi deficiency syndrome in PNS, which is consistent with previous studies [18]. According to TCM theory, Qi deficiency is involved in the pathogenesis of nephrotic syndrome, and blood stasis acts as a key pathological factor to further complicate the condition [8]. A TCM syndrome study in PNS showed that Qi deficiency is one of the most common TCM syndrome types, whose score correlated significantly with higher urine protein/creatinine ratio and TC level [19].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…is indicates the importance of blood stasis syndrome and Qi deficiency syndrome in PNS, which is consistent with previous studies [18]. According to TCM theory, Qi deficiency is involved in the pathogenesis of nephrotic syndrome, and blood stasis acts as a key pathological factor to further complicate the condition [8]. A TCM syndrome study in PNS showed that Qi deficiency is one of the most common TCM syndrome types, whose score correlated significantly with higher urine protein/creatinine ratio and TC level [19].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, recommended treatments for PNS can also cause unwanted side effects [5][6][7]. Traditional Chinese medicine (TCM) has been documented to have a beneficial effect for PNS diagnosed based on individual symptoms, but not the pathological type; thus, TCM might be a potential adjuvant or alternative treatment for PNS [8][9][10]. Chinese herbal injections (CHIs) are innovative formulations of herbs with high bioavailability and rapid action that are widely administered in China [11].…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ]. This herb possesses many common pharmacological activities, such as multiple organ protection [ 4 , 5 ], antioxidant [ 6 ], hypoglycemic [ 7 ], antiviral [ 8 ] and so on, and has their own pharmacological properties and mechanisms. Studies have shown that A. membranaceus can enhance the contraction of the right ventricular myocardium in rats in a dose-dependent manner [ 9 ] and has recently been reported to be a potential promote tissue wound repair.…”
Section: Introductionmentioning
confidence: 99%
“…According to its histological characteristics, NS can be classified into several types including minimal change disease, membranous proliferative glomerulo-nephritis, focal segmental glomerulosclerosis, and membranous nephropathy [4]. The annual incidence of NS has been estimated to be 3 per 100,000 adults and 2-7 per 100,000 children, posing an enormous burden on both society and individuals due to the high risk for the progression of end stage renal disease [5,6]. The main therapeutic agents for NS are glucocorticoids, immunosuppressants and cytotoxic drugs.…”
mentioning
confidence: 99%
“…The limited success of clinically available therapies for NS highlights the pressing requirement for the development of more effective and safer alternative agents. Thanks to the low side effects, rich resource and remarkable efficacy of traditional Chinese medicine (TCM), TCM, as one of the major modalities in complementary and alternative medicine, has a long history for treating a variety of nephropathies [6,8,9]. Network pharmacology is a systematic approach, which is used to understand the complexities among compounds, targets, diseases and biosystems [10].…”
mentioning
confidence: 99%